2013
DOI: 10.4049/jimmunol.1200856
|View full text |Cite
|
Sign up to set email alerts
|

Proteolysis of Complement Factors iC3b and C5 by the Serine Protease Prostate-Specific Antigen in Prostatic Fluid and Seminal Plasma

Abstract: Prostate-specific Ag (PSA) is a serine protease that is expressed exclusively by normal and malignant prostate epithelial cells. The continued high-level expression of PSA by the majority of men with both high- and low-grade prostate cancer throughout the course of disease progression, even in the androgen-ablated state, suggests that PSA has a role in the pathogenesis of disease. Current experimental and clinical evidence suggests that chronic inflammation, regardless of the cause, may predispose men to prost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 29 publications
0
18
0
Order By: Relevance
“…Sublytic complement C5b-9 protects prostate cancer cells from tumour necrosis factor-α-induced cell death 82 . Interestingly, proteolysis of iC3b and C5 by the serine protease prostate-specific antigen in prostatic fluid was detected, inhibiting the terminal pathway 83 .…”
Section: Cancers With "Protective Complement"mentioning
confidence: 99%
“…Sublytic complement C5b-9 protects prostate cancer cells from tumour necrosis factor-α-induced cell death 82 . Interestingly, proteolysis of iC3b and C5 by the serine protease prostate-specific antigen in prostatic fluid was detected, inhibiting the terminal pathway 83 .…”
Section: Cancers With "Protective Complement"mentioning
confidence: 99%
“…Of note, biochemical evaluation of this C3 cleavage fragment revealed a putative prostate-specific antigen (PSA) cleavage site. Indeed, purified PSA was able to cleave C3 and C5 in vitro , suggesting that PSA acts as an immunoregulatory protease that contributes to a pro-tumorigenic environment through the proteolysis of complement proteins 125 .…”
Section: Challenges Of Translational Researchmentioning
confidence: 99%
“…It could not be confirmed that PSA had a role in the pathogenesis of this disease until a C3 cleavage site was discovered by biochemical analysis with tryrosine-1348. Furthermore, purified PSA was able to cleave iC3b and the associated complement protein C5 [49]. These results revealed that PSA as an immune inhibition protease could assist to create a micro-environment beneficial to malignancy through degradation of the complement components.…”
Section: ) Degradation Of Complement Componentsmentioning
confidence: 82%
“…A prostate-specific antigen (PSA) was found to continually express in high-level among the majority of men with both high-and low-grade prostate cancer [49]. It could not be confirmed that PSA had a role in the pathogenesis of this disease until a C3 cleavage site was discovered by biochemical analysis with tryrosine-1348.…”
Section: ) Degradation Of Complement Componentsmentioning
confidence: 99%